Potential Therapeutic Approaches for the Treatment of Acute Myeloid Leukemia with AML1-ETO Translocation - Arora, Rashi; Sawney, Sharad; Saluja, Daman (Current Cancer Drug Targets, 2016)
Background: Twenty percent of patients with Acute Myeloid Leukemia (AML) carry a translocation between chromosomes 21 and chromosome 8 resulting in the formation of a chimeric oncoprotein AML1-ETO. The patients with this translocation although have a favourable prognosis, but the 5-year survival is only about 50%. It is anticipated that identification of novel therapeutic targets in t(8;21) positive AML will lead to treatment options that improve patient survival. Areas covered: The oncoprotein and the proteins required to maintain its stability and functionality are the first obvious therapeutic targets. Further, newer technologies like combining gene expression and DNA occupancy profiling assays, gene expression–based high-throughput screening, etc have led to identification of proteins or pathways that are required by AML1-ETO for leukemogenesis and the agents that modulate these proteins to be considered good candidates for targeted molecular therapy. Various FDA approved drugs and secondary metabolites derived from traditional medicinal plants have been shown to possess anti-proliferative effect on t(8:21) harboring leukemic cell lines. Conclusion: In order to improve the therapeutic regime for AML patients with t(8;21), efforts are required to translate the success achieved in identification of potent candidates for targeted therapy into clinical setup in the best possible combination.
Keywords: potential target